Implementasi Pembelajaran Coding Dan Kriptografi Pada Pesan Digital di SMA Negeri 2 Mataram - Maulani Rizqi; Intan Nadilah; Ahmadil Hamdi; Nikken Prima Puspita; I Gede Adhitya Wisnu Wardhana (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to increase the understanding of students at State Senior High School 2 Mataram regarding information security by introducing the concepts of coding and cryptography in digital messages. The rapid use of messaging applications among teenagers makes students increasingly vulnerable to cyber threats, necessitating education on how data protection works in online communication. This program is implemented using a descriptive method consisting of planning, implementation, and evaluation stages. The material covered includes basic cryptography concepts, end-to-end encryption mechanisms, and the practical process of the Diffie–Hellman key exchange thru the interactive simulation